Florida 4-H Community Pride Leader's Guide - Stacey Ellison; Grace Carter (EDIS, 2019)
Service learning is an important component of youth development because it allows youth to strengthen their critical thinking skills, leadership skills, and civic and social responsibility. This 5-page Leader's Guide will help you and your club members get the most out of the Community Pride Program. Written by Stacey Ellison and Grace Carter, and published by the UF/IFAS 4-H Youth Development Department, January 2019. Updated with new contact person, March 2020. http://edis.ifas.ufl.edu/4h396